Efektivitas Pembelaaran PJOK Pada Teknik Dasar Voli Melalui Materi Virtual Di Selama Pandemi Covid-19 - Nurkadri Nurkadri; Farhan Alba Asith; Ilham Ariba; Joshua Sitompul; Samira Samira; Tuahta Mario Eka Putra (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Physical education is an integral part of the entire educational process through selected physical activities to develop and improve three domains, namely: cognitive, affective, and psychomotor. PJOK learning is learning that is more than just teaching knowledge from a teacher to students, more than that in this learning process an educator is expected to be able to optimize the potential that exists in students. One solution that can be applied so that the learning process can continue is to carry out the learning process through online media. This research method uses descriptive qualitative research, descriptive research is a research conducted with the main objective to provide an overview or description of a situation objectively. Data collection in this study was carried out by collecting articles, information, or from books. Data collection in this study was carried out by downloading articles and journals related to it. Based on the research that has been done, the effectiveness of PJOK learning on the basic technique of passing down the volleyball game through online media for class VIII students of SMP Widya Sakti Denpasar is said to be effective when viewed from the values of assignments and students' practice. From the attitude of the teacher in the learning process, the teacher has been very maximal in providing material to students. but the teacher has not found a solution so that students become better for online learning without the obstacles of facilities and infrastructure that exist in each student's home.